Gene therapy with B‐cell maturation antigen/CD3 bispecific antibody encoding plasmid DNA for treating multiple myeloma. (20th May 2022) - Peng, Fengping; Wang, Yuan; Zhao, Jiliang; Liu, Hui; Liu, Zhaoyun; Ding, Kai; Zhang, Hongkai; Fu, Rong
Summary: The delivery of bispecific antibodies (BsAbs) targeting B‐cell maturation antigen (BCMA) and CD3 using the gene therapy approach is a promising alternative for BsAb administration in patients with multiple myeloma (MM). In the present study, we evaluated the efficacy of this approach using a xenograft model. Tumour growth was significantly delayed in mice treated with single electroporation‐enhanced intramuscular injection of plasmid DNA encoding BCMA/CD3 BsAb in contrast to the vehicle control‐treated group. Limited toxicity was observed following treatment. This study demonstrates that the gene therapy‐based approach for the delivery of BCMA/CD3 BsAb is effective and safe for the treatment of MM.